Type 2 Diabetes Mellitus: A Review of Determinants, Pathophysiology, Diagnostics, Management, and Complications - Prasetyo, Budi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The prevalence and incidence of diabetes mellitus are both on the rise, making it a continuing problem on a global scale. There are multiple factors that contribute to the development of type 2 diabetes mellitus. The disease is characterized by the presence of both a genetic component and an equally significant environmental component. A process of chronic hyperglycemia is the first step in the development of diabetes mellitus. This hyperglycemia is caused by the inability of pancreatic beta cells to secrete insulin, as well as insulin resistance in the muscles and the liver. Diabetes Mellitus Type 2 that is not treated with either medication will result in a variety of problems, including chronic consequences such as microangiopathy, retinopathy, nephropathy, and macroangiopathy. These complications can be caused by a number of different factors. The determinants, pathophysiology, diagnosis, management, and complications of type 2 diabetes mellitus are all topics that are covered in this study.